Study of a debris torrent in the Dolomites, Italy - Biscuola, Elena; Turrini, Maria Chiara (Journal of Nepal Geological Society, 2000)
The Dolomites are situated in a region characterised by the presence of widespread debris flows, which originate at the foot of sub-vertical rocky walls and involve the underlying debris talus. These flows are characterised by the scantiness of the planimetric surface in the watershed and, when they are not channelled, by the variability of the courses from one event to another. This paper describes the study of a channelled debris flow or debris torrent, which periodically jeopardises the built-up area of San Vigilio di Marebbe (Bolzano). This town is located on a large alluvial fan formed by the torrents Ermo and Fojed6ra. The beds of both torrents are constantly full of debris, which is partly contained by many dams and mostly carried away by the water that undercuts the banks. The Fojedora, in particular, which until 1971 ran through the town carrying with it considerable amounts of debris, regularly damaged the town. As a result of these incidents, the last part of the course of the Fojed6ra was artificially diverted into the Ermo by the construction of a 4 m high and 320 m long dyke. In this way the flows, which continued to run through the torrent in the following years, were confined in the channel, and the only danger was that posed by the damming of the main channel into which the torrent Fojed6ra-Ermo flows. The last important event took place on 27 July 1995 following a short but bad cloud burst in the upper reaches. It mobilised a considerable amount of debris and gave rise to a flow, which was contained by the dyke, and temporarily obstructed the main torrent and the valley floor. The aim of the study was to reveal the mechanisms that might trigger off the flows, to analyse the morphometry of the deposits in order to characterise these deposits in terms of grain size, and to assess the possibility of damage to the infrastructure. The work was carried out in the following phases: - a historical reconstruction of past events from both historical documents and the "memories" of the oldest inhabitant s of the town: - a study of the precipitation records of two meteorological stations located near the landslide area; and - a topographical reconstruction of the flow route in order to map the main morphological elements , such as channels, scarps, banks, and lobes, and to carry out the grain size analysis of sediments. Detailed mapping of the alluvial fan by mean s of overlaying slope and land use maps was aimed at evaluating whether a possible flow that was not contained by the dyke might reach San Vigilio di Marebbe.